The interaction between financial incentives and task-specific cognitive capital: more evidence in support of Camerer and Hogarth (1999) - Ondřej Rydval (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper extends existing evidence on the interaction between financial incentives and cognitive capital. I focus on the impact of task-specific cognitive capital, the role of which is central to the capital-labor-production framework of Camerer and Hogarth (1999) and has long been studied in cognitive science and behavioral decision research. Using a task situated in an accounting setting, I show that both financial incentives and task-specific cognitive capital, and especially their interaction, matter for performance. In particular, the effect of task-specific cognitive capital on performance is stronger under performance-based financial incentives as compared to flat-rate incentives. The interaction effect arises because performance-based financial incentives lead to better performance only for individuals with more task-specific cognitive capital. I draw implications for compensation practices in experiments as well as work settings.
Keywords: C81; C91; C93; D83; 330; Financial incentives; Cognitive abilities; Experiments; Field experiments; Ökonomischer Anreiz; Beschränkte Rationalität; Kognition; Test